2007
DOI: 10.1002/masy.200751323
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Swelling of Poly(D,L‐lactic acid) and Poly(lactic‐co‐glycolic acid) in Supercritical CO2

Abstract: Summary:The equilibrium sorption and swelling behavior in supercritical CO 2 of poly(D,L-lactic acid) and poly(lactic-co-glycolic acid) has been studied at a temperature of 35 8C and at pressures up to 200 bar. Sorption was measured through a gravimetric technique and swelling by visualization. From these data, the behavior of the different polymers can be compared. In terms of partial molar volume of CO 2 in the polymer matrix, all the polymers exhibit a behavior typical of rubbery systems. The experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…This indicated that P DL LA had the greatest interaction with CO 2 and the interaction decreased with the increase of GA content in the polymers. This is in good agreement with the results obtained from the sorption and swelling studies, in which the solubility of CO 2 in PLGA copolymers was found to decreases with the increase in the glycolic acid content (Pini et al, 2007;Pini et al, 2008). The interaction of polymers with CO 2 is dependent upon the chemical structure.…”
Section: Co 2 Solubility In Pla and Plgasupporting
confidence: 91%
See 2 more Smart Citations
“…This indicated that P DL LA had the greatest interaction with CO 2 and the interaction decreased with the increase of GA content in the polymers. This is in good agreement with the results obtained from the sorption and swelling studies, in which the solubility of CO 2 in PLGA copolymers was found to decreases with the increase in the glycolic acid content (Pini et al, 2007;Pini et al, 2008). The interaction of polymers with CO 2 is dependent upon the chemical structure.…”
Section: Co 2 Solubility In Pla and Plgasupporting
confidence: 91%
“…The sorption and swelling of PLA and PLGA polymers have been studied using different measurement techniques and also simulated using different mathematical modeling. These include a quartz crystal microbalance for the measurement and a dualmode sorption model and Flory-Huggins equation for modelling used by Oliveira and coworkers ; an external balance for the measurement and perturbed-hard-sphere-chain equation of state for modeling used by Elvassore and coworkers (Elvassore et al, 2005); and a pressure decay technique for the measurement and Sanchez-Lacombe equation of state for modeling used by Liu and coworkers (Liu &Tomasko, 2007 Pini et al studied the solubility of amorphous P DL LA and PLGA polymers (Table 1) at 35 o C and up to 200 bar by measuring their sorption and swelling in CO 2 using a magnetic suspension microbalance and visualization method, and the Sanchez-Lacombe equation of state was used for correlating the experimental data (Pini et al, 2007;Pini et al, 2008). The P DL LA homopolymer shows the largest values of sorption and swelling (sorption and fractional swelling up to 0.5 g CO 2 /g polymer and 0.68, respectively, at 200 bar), whereas the PLGA5050 has the lowest affinity to CO 2 ( Figure 2).…”
Section: Co 2 Solubility In Pla and Plgamentioning
confidence: 99%
See 1 more Smart Citation
“…The samples of PLA investigated in this study had higher swelling extent in scCO2 in comparison to previously reported at comparable pressure and temperature conditions (density of CO2) [1,11,12].…”
Section: Figure 2 -Swelling Kinetics Of Pla Monolithcontrasting
confidence: 42%
“…PLA (PLA 52K, Purac) investigated by Pini and coworkers [11] had maximum swelling extent of 0.65% at 35 °C and 20 MPa, while swelling extent of PLA (PLA 15K, Resomer, and PLA 52K, Purac) investigated by Tai and coworkers [1] at same conditions was up to 0.68%. Sato and coworkers [12] reported 0.20-0.55% swelling extent of PLA (PLA 117K and 157K, Mitsui Chemicals, Inc.) at 40 °C and 6-20 MPa.…”
Section: Figure 2 -Swelling Kinetics Of Pla Monolithmentioning
confidence: 99%